Relating microfossil distribution patterns to deep-water depositional processes: a new biofacies model based on Oligocene-Miocene deposits - Knabe, K. A.; Chen, Y.-Y; Huang, T.-C; Beaubouef, R. T. (Anuário do Instituto de Geociências, 2006)
Abstract